Modified Nucleosides 2008
DOI: 10.1002/9783527623112.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Locked Nucleic Acids: Properties, Applications, and Perspectives

Abstract: A decade has passed since the introduction of locked nucleic acid (LNA) [1][2][3]. This chapter provides a review and a current status on the features and applications of LNA. Attention is focused on the structural chemistry of LNA and on its applications for therapeutics and probes. With regards to the latter point, the chapter is based on former comprehensive reviews on LNA applications [4][5][6] and, for that reason, is focused on results reported subsequently, with no intention of being comprehensive.The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…It adds to this importance that the stabilization increases with two consecutive modifications of 1 or 2 . For the development of antisense oligonucleotides, 1 and 2 can easily be combined with other modifications such as LNA and phosphorthioates that in combination has proven very promising in antisense research . LNA monomers induce a larger increase in thermal stability of DNA:RNA duplexes than the nucleobase substituents of 1 and 2 , but the two kinds of modifications show opposite behavior, as the impact of an LNA monomer is largest by one incorporation and then decreasing, relatively, by the number of consecutive incorporations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It adds to this importance that the stabilization increases with two consecutive modifications of 1 or 2 . For the development of antisense oligonucleotides, 1 and 2 can easily be combined with other modifications such as LNA and phosphorthioates that in combination has proven very promising in antisense research . LNA monomers induce a larger increase in thermal stability of DNA:RNA duplexes than the nucleobase substituents of 1 and 2 , but the two kinds of modifications show opposite behavior, as the impact of an LNA monomer is largest by one incorporation and then decreasing, relatively, by the number of consecutive incorporations.…”
Section: Discussionmentioning
confidence: 89%
“…The idea of regulating gene expression by chemically modified oligonucleotides has been pursued for three decades. , The therapeutic potential has been formulated in the so-called antisense , and antigene strategies, where the molecular target is RNA and genomic double stranded DNA, respectively. The chemically modified oligonucleotides should be physiologically stable and form thermally strong duplexes with RNA or triplexes with DNA. , A significant amount of chemical modifications have been presented, and among the most successful are 2′-modified nucleotides, conformationally restricted carbohydrate moieties, as in LNA, and base-modified analogues . As a prime example of the latter, nucleobases with extended ring systems have been found to give very strong duplexes due to increased π–π stacking.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing one or more LNA−nucleoside monomers into an otherwise unmodified oligodeoxynucleotide, unprecedented recognition of complementary RNA and DNA has been obtained. The increase in thermal stability (Δ T m ) of the formed duplexes compared to unmodified duplexes ranges from +3 to +8 °C for each incorporation of an LNA monomer. , It has been demonstrated that each LNA−nucleoside monomer is able to conformationally tune its neighboring unmodified 2′-deoxynucleosides from S - to N -type conformations (Figure ) . By this means, the overall duplex conformation is driven toward A-type or A-type-like duplex forms by the introduction of only a few LNA nucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotides that are conformationally restricted due to bicyclic nucleoside building blocks have demonstrated unique molecular recognition of complementary nucleic acid sequences and thus very promising properties as, e.g., antisense oligonucleotides (AOs), siRNA, or triplex-forming oligonucleotides (TFOs) . More than any other nucleic acid analogue, locked nucleic acid (LNA) has been recognized as the prime tool for engineering strong and specific nucleic acid recognition. , LNA constitutes only a small structural perturbation to natural nucleic acids, and its preparation is completely compatible with standard solid-phase DNA synthesis. The LNA nucleoside monomer (Figure , 1 ) is a bicyclic nucleoside that is locked in an N -type conformation due to an oxymethylene bridge between the 2′- and 4′-positions.…”
Section: Introductionmentioning
confidence: 99%